Occlusal characteristics and sex prediction potential of maxillary posterior teeth in Malay population - Riaz, Samiya (2023)
Forensic dentistry has two aspects of human identification i.e., comparative identification and dental profiling (age, sex, and race estimation). This study aimed to determine bilateral symmetry, sexual dimorphism, and sex prediction in the maxillary posterior teeth of Malay population using two-dimensional (2D) and threedimensional (3D) methods. This study also determined the uniqueness of groove pattern (GP) and occlusal table (OT) of teeth for human identification. In total, 176 dental casts were converted to digital images and dental scans using Hirox KH7700 digital stereomicroscope (Japan) and Medit i500 intraoral scanner (Medit Corp, South Korea). The cusp area, crown area, cusp number (CN), and GP were recorded using 2D Hirox, while the cusp area and the surface OT area were measured using 3-Matic software (Materialise NV, Belgium). For uniqueness, digital tracings of GP were superimposed using 2D Hirox stereomicroscope, while OT of dental scans were superimposed using Cloudcompare software (Cloudcompare, Paris, France). There was no significant difference between the left- and right-sided teeth in both the 2D and 3D methods (p > 0.05) for all tested parameters. There was statistically significant difference between male and female in both 2D and 3D methods (p < 0.01) for all tested parameters of cusp and crown area. The sex prediction classification accuracy was 80% for the cusp and crown areas in the 2D method while the accuracy was 82.7% for the cusp and OT area in 3D method. There were no significant differences between the CN, GP, and OP of the left- and right-sided teeth (p > 0.05), and the CN between Zmale and females (p > 0.05). There was a significant difference in the GP and OP of first premolar (PM1) and second premolar (PM2) between male and female (p < 0.05). However, there was no significant difference in the GP and OP of first molar (M1) between male and female (p > 0.05). Sex classification accuracy was 62.7% for the CN, GP, and OP of maxillary posterior teeth. The GP showed 100% uniqueness for PM1, PM2, and M1. The OT topography showed 100% uniqueness for PM1, PM2, and M1. Similarly, the OT showed statistically significant difference (p<0.01) between the root mean square (RMS) values of the matched and non-matched pairs. In conclusion, the maxillary posterior teeth in Malay population showed significant sexual dimorphism and sex determination potential. The GP and OT of maxillary posterior teeth show 100% uniqueness that indicated both parameters are useful for human identification.